2015
DOI: 10.1016/j.onehlt.2015.07.002
|View full text |Cite
|
Sign up to set email alerts
|

Flying-foxes in the Australian urban environment—community attitudes and opinions

Abstract: The urban presence of flying-foxes (pteropid bats) in eastern Australia has increased in the last 20 years, putatively reflecting broader landscape change. The influx of large numbers often precipitates community angst, typically stemming from concerns about loss of social amenity, economic loss or negative health impacts from recently emerged bat-mediated zoonotic diseases such as Hendra virus and Australian bat lyssavirus. Local authorities and state wildlife authorities are increasingly asked to approve the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
36
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(38 citation statements)
references
References 16 publications
2
36
0
Order By: Relevance
“…For example, in one instance there was a "neighbourhood war basically between two neighbours, one who loved the bats and one who hated them" (Interview #8). This is consistent with other research on the perceptions of bats [20,21] which found they were "very different things to different people" [37]. Instances such as these highlight the presence of differing values for wildlife, which makes decision-making about the appropriate response very challenging.…”
Section: Factors Influencing Decision-makingsupporting
confidence: 89%
“…For example, in one instance there was a "neighbourhood war basically between two neighbours, one who loved the bats and one who hated them" (Interview #8). This is consistent with other research on the perceptions of bats [20,21] which found they were "very different things to different people" [37]. Instances such as these highlight the presence of differing values for wildlife, which makes decision-making about the appropriate response very challenging.…”
Section: Factors Influencing Decision-makingsupporting
confidence: 89%
“…The former is a consequence of the noise, soiling and smell typically attendant with large numbers of flying‐foxes; the latter primarily reflects public concern about bat‐mediated zoonotic diseases such as Hendra virus and Australian bat lyssavirus, both of which have caused sporadic human fatalities. (Kung et al, 2015, p. 24)…”
Section: Urbanisation and Health Securitymentioning
confidence: 99%
“…Kilpatrick (2011) shows how Culex pipiens (the common house mosquito), which carries the West Nile virus, increase in numbers with urbanisation. In Australia, Firth and Zuelke (2014) discuss how possums are a major source of zoonotic bacteria in drinking water and, also in Australia, Kung et al (2015) show how the urban presence of ‘flying‐foxes’ (pteropid bats) present risks for public health. The species have become increasingly urbanised in the past 20 years due to changes in the rural landscape.…”
Section: Urbanisation and Health Securitymentioning
confidence: 99%
“…Several local councils face the challenges of mitigating the impacts of flying-fox camps on their communities (e.g. Hall 2002;Roberts 2006;Kung et al 2015). The management of these issues requires councils to find a balance between legal obligations, conservation of a threatened species and the needs of the community (Thiriet 2010;Holmes and Walker 2011;Currey et al 2018).…”
Section: Reflections On the Management Of The Kareela Flying-fox Campmentioning
confidence: 99%
“…However, this action would not be consistent with conservation objectives nor community amenity objectives. Based on the complexity and challenges involved in flying-fox camp dispersal, this option is rarely deemed an appropriate management action by informed stakeholders (Kung et al 2015).…”
Section: Reflections On the Management Of The Kareela Flying-fox Campmentioning
confidence: 99%